English as a global language: Students’ perceptions in the age of digital communication - Tri Septiana Kurniati; Asha Parmar; Agustina Ratri Probosini; Eli Irawati; Irma Diani (Journal of Research in English Language Teaching and Linguistics, 2026)
English has become a central medium for global communication, especially in digitally connected environments where interaction occurs across linguistic and cultural boundaries. Recent studies highlight a shift from viewing English as a fixed system to understanding it as a flexible, experience-driven resource shaped by everyday use. However, limited attention has been given to how students themselves interpret and experience English in real digital contexts, particularly in relation to communication practices, identity, and confidence. This study aims to explore students’ perceptions of English as a global language in the age of digital communication, focusing on how they use, understand, and value the language in their daily lives. The study employed a qualitative research design involving 27 students. Data were collected through open-ended surveys that captured students’ experiences, attitudes, and reflections on using English in digital environments. The data were analyzed using thematic analysis, allowing patterns and meanings to emerge from participants’ responses through systematic coding and interpretation. The findings reveal that students perceive English as a practical and meaningful tool for communication and access to information, especially in online spaces. They tend to prioritize meaning over accuracy, using English in relaxed and informal ways while gradually developing flexibility and confidence through repeated exposure. At the same time, traces of formal learning remain, particularly in their concern for correctness. English also serves a personal function, enabling self-expression and fostering a sense of connection to a global community, although some students still experience anxiety and occasional misunderstandings. These findings suggest that English learning is increasingly shaped by digital interaction and personal experience. The study highlights the need for pedagogical approaches that balance accuracy with communicative flexibility, while also recognizing students’ lived experiences and emotional engagement in using English.